Evaluation Of Antiurolithiatic Activity Of Methanolic Seed Extracts Of Persea Americana Against Calcium Oxalate Induced Urolithiasis In Rats (Journal of Pharmaceutical Negative Results, 2022)
Objective: Persea Americana methanolic seed extracts are considered for the present study to access its efficacy, urolithiasis is inducedby administering the male rats with calcium oxalate.Methods: Calcium oxalate urolithiasis is induced in male rats by means of hyperoxaluria model by administering ethylene glycol of0.75% v/v, with 1% w/v ammonium chloride supplemented in drinking water for 3 days followed by 0.75% v/v of ethylene glycol for25 days. The PAMSE is administered to urolithiasis induced test group at dose of 150mg/kg respectively for 28 days.Results: As anticipated after 28 days the calcium oxalate is deposited significantly in the kidney which is associated with the increaseof Urinary oxalate, Urine calcium & magnesium levels, serum uric acid, creatinine in urolithiasis control groups. ACP, ALP, AST &ALT well known biochemical parameters are seen to be increased with decreased level of LDH assessed using kidney homogenate,copiously confirming the induction of urolithiasis , its promising to know that the PAMSE intubation to the test group daily decreasedthe quantity of formation of calcium oxalate and all the biochemical changes induced by urolithiasis is reverted.Conclusion: Results from this study shows that PAMSE is effective inhibitor of crystallization of calcium oxalate comparable to thestandard Cystone in dose dependent mode. Therefore indicating PAMSE’s significant antiurolithiatic activity.